Human-in-the-loop single-sided exoskeleton simulation - Raymondal, Sankalpa (Nanyang Technological University, 2024)
Assistive exoskeletons can assist in mobility-related disabilities and with the increasing elderly population who experience such problems, exoskeleton demand will increase. Human-in-the-loop simulations can accelerate the exoskeleton development process for quicker availability of exoskeletons for mobility-affected patients. In this project, a state-of-the-art human-in-the-loop simulator platform with the unique feature of generating human models that replicate patient body anatomy and gait is extended with the ability to include an exoskeleton model. To achieve this simulation, the digital twin of the exoskeleton model is obtained by converting its CAD model to a simulation-usable model. It is then integrated with the human model using constraints defined in the physics simulator in use, MuJoCo. Then, the control policy developed for the exoskeleton is reproduced such that the real-world experiments are replicated in simulation. Various issues related to convex hulls or insufficient friction in joints of the exoskeleton model are solved while obtaining the exoskeleton’s digital twin. The challenges in making the integrated model walk in simulation are explored and simplifications are made. The gravity compensation control policy of the exoskeleton is implemented, successfully replicating real-world experiments in simulation. The walking of the integrated model is then evaluated with and without the exoskeleton control policy. The integrated model walks stably without gravity compensation, while its application leads to instability, resulting in falls. Potential factors contributing to this phenomenon include abrupt changes in the torque applied by the exoskeleton, leading to imbalance.